What makes acute cholecystitis recur after removing the percutaneous cholecystostomy tube?. Issue 5 (4th February 2022) - Heo, Jun; Jung, Min Kyu; Cho, Chang Min; Lee, Sang Yub; Ryeom, Hun Kyu; Chun, Jae Min; Han, Young Seok; Kwon, Hyung Jun
Abstract : Abstract: Percutaneous transhepatic gallbladder drainage (PTGBD) is an alternative treatment option for acute cholecystitis. However, the disease may recur after PTGBD catheter removal. This study aimed to evaluate the role of endoscopic sphincterotomy and other risk factors in reducing the recurrence of cholecystitis. We retrospectively analyzed data from 1088 patients who underwent PTGBD for cholecystitis at Kyungpook National University Hospital, Republic of Korea, between January 2011 and April 2018. A total of 115 patients were enrolled in the study. The recurrence rate of cholecystitis was 17.4% (n = 20) during a median follow-up period of 1159 (range, 369–2774) days. Endoscopic biliary sphincterotomy did not significantly affect the recurrence rate of cholecystitis ( P  = .561). In multivariable analysis, cystic duct stones ( P  = .013) and PTGBD catheter migration before the prescheduled removal time ( P  = .002) were identified as independent risk factors for cholecystitis recurrence after PTGBD. To reduce post-PTGBD recurrence in cholecystitis, caution must be exercised to avoid inadvertent dislodging of the PTGBD catheter. In cases of cholecystitis with cystic duct stones, cholecystectomy should be considered only after careful assessment of postoperative risks. Instead, transluminal endoscopic gallbladder drainage could represent a promising option for the prevention of recurrent cholecystitis.